Real‐Time In Situ Powder X‐ray Diffraction Monitoring of Mechanochemical Synthesis of Pharmaceutical Cocrystals1. Issue 44 (23rd September 2013) - Halasz, Ivan; Puškarić, Andreas; Kimber, Simon A. J.; Beldon, Patrick J.; Belenguer, Ana M.; Adams, Frank; Honkimäki, Veijo; Dinnebier, Robert E.; Patel, Bhavnita; Jones, William; Štrukil, Vjekoslav; Friščić, Tomislav
<x xml:space="preserve">Abstract</x> Looking in: The penetrating power of high‐energy X‐rays provides a means to monitor in situ and in real time the course of ball‐milling reactions of organic pharmaceutical solids by detecting crystalline phases and assessing the evolution of their particle sizes. Upon switching from neat grinding to liquid‐assisted grinding, cocrystal formation is enabled or tremendously accelerated, while the reaction mechanism alters its course.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>